Clinical Pharmacology Research Internships at the Interface between Academia and Industry: Students' Perceptions and Scientific Output. Issue 1 (8th March 2017) - Goulooze, Sebastiaan C.; Franson, Kari L.; Cohen, Adam F.; Rissmann, Robert
Abstract: The Centre for Human Drug Research (CHDR) is a non‐profit clinical research institute at the interface between academia and the pharmaceutical industry. CHDR hosts a research internship programme for undergraduate (bio)medical students. The aim of this study was (i) to investigate the student perceptions of the undergraduate research internship and (ii) to quantify the scientific output related to these internships. We surveyed former interns at the CHDR from the year 2007 to 2014 and quantified their scientific output with a PubMed search. There was a response rate to the survey of 61%, with a good overall rating of the internships. Many students considered their internship at CHDR to be (much) more broad (55%) and with a (much) stricter planning (48%), compared to previous internships at academic research groups. In turn, there were many aspects reported to be similar to academic research internships such as focus on research methodology and 'outcome‐drivenness'. Twenty‐four per cent of the internships resulted in a co‐authorship on papers published in peer‐reviewed journals with an average impact factor of 3.3. In conclusion, with appropriate management and supervision, effective research electives are possible in the more commercial environment of a clinical research organization.